Typology Of Detached Constructions In English - Sobirova Nigina Aliyevna (Zien Journals, 2025)
This article discusses the typology of detached constructions in English. Detached constructions are a stylistic phenomenon indicating the lateness of the speaker’s speech. When studying detached constructions in English, attention is paid to their formal and semantic features. An important principle of the article is the study of the important features of this phenomenon in the typology of English-language detached constructions and their interpretation with the identification and generalization of features based on their comparison. Detached constructions are also studied by comparing the device with other linguistic phenomena. The article describes exactly the same events in detail.
Keywords: Detached construction; typology; semantic feature